Changes in the macroscopic morphology of hip muscles in low back pain - Pourahmadi, Mohammadreza (J Anat, 2019)
Low back pain is a major health issue affecting the lumbopelvic muscles. Morphological changes in hip muscles, such as alterations in the muscle cross‐sectional area and muscle volume, may occur in patients with low back pain. This systematic review was conducted to investigate whether patients with low back pain have macroscopic changes in their hip muscle morphology compared with asymptomatic, healthy individuals, based on current evidence. The electronic databases of PubMed/Medline, Ovid, Scopus, Embase(®), and Google Scholar were searched from the inception to August 31, 2018. We only included full texts of original studies regarding macroscopic morphological alterations, including atrophy and fat infiltration, in hip muscles of patients with low back pain compared with asymptomatic controls. The quality of the included studies was determined using an assessment tool based on the Newcastle–Ottawa Scale. The scale was modified for the purposes of this study. Sixteen comparative observational studies were found eligible to be included in this review. Eleven were classified as high quality and four as moderate quality. The morphological changes in the psoas major, gluteus maximus, gluteus medius, gluteus minimus, and piriformis muscles were assessed in the primary studies. All selected studies were considered B level of evidence studies. The strength of conclusions for the psoas major, gluteal, and piriformis muscles was moderate. The results revealed that there is substantial controversy about the morphological changes in hip muscles in patients with low back pain; however, the majority of high‐quality studies concluded that atrophy of hip muscles is evident in patients with low back pain. The psoas major muscle was the most commonly investigated hip muscle for morphological changes. Major methodological limitations of the included studies were identified and discussed. The present systematic review does not include a formal meta‐analysis because of very significant differences in the primary studies in terms of study populations and methodologies. Finally, in clinical practice, it is recommended that physical therapists develop exercise programs to improve hip muscle function in patients with low back pain.